Students’ Perception of Vocabulary Mastery by Using Baamboozle Game - Tanjung, Rahmi Rahmita; Daulay, Sholihatul Hamidah (Institut Agama Islam Negeri Palopo, 2025)
This study explores vocational high school students’ perceptions of using Baamboozle for vocabulary learning. While gamification is effective, research on students' perspectives remains limited. Using a qualitative case study, 20 students completed a questionnaire, and five participated in interviews. Thematic analysis identified key trends. Findings show Baamboozle enhances engagement, motivation, comprehension, and retention, making learning enjoyable. However, some students noted unequal participation in group activities. These results align with Constructivist Learning Theory, emphasizing interactive learning. This study contributes to game-based learning research by providing insights into Baamboozle’s impact. Future studies should explore long-term effects and compare it with other digital tools. Educators should integrate Baamboozle with structured strategies for optimal results.